2002
DOI: 10.1051/0004-6361:20021156
|View full text |Cite
|
Sign up to set email alerts
|

Do dynamo-waves propagate along isorotation surfaces?

Abstract: Abstract. It is shown that the basic rule of the dynamo theory on the propagation of dynamo-waves along surfaces of constant angular velocity is restricted to the case of isotropic magnetic diffusion. The influence of rotation on convective turbulence induces an anisotropy in the eddy diffusivity. The anisotropy makes the direction of travel of the dynamo wave deviate from the isorotation surfaces. The deviation is towards the equator for solar conditions. This finding may help to resolve the old problem of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…This could be expected from the analysis given by Kitchatinov (2002). In our calculations, parameter (a) controls the excess of the magnetic diffusivity in the horizontal direction relative to the vertical direction.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This could be expected from the analysis given by Kitchatinov (2002). In our calculations, parameter (a) controls the excess of the magnetic diffusivity in the horizontal direction relative to the vertical direction.…”
Section: Discussionsupporting
confidence: 53%
“…It transfers the energy of magnetic fields from large to small scales and determines the characteristic spatial scale of the excited dynamo modes (see Parker 1971 and the reviews of Brandenburg & Subramanian 2005;Charbonneau 2011). The magnitude of turbulent diffusion impacts the period of the dynamo cycle, and the anisotropy of turbulent diffusion affects latitudinal drift of the large-scale magnetic field during the activity cycle, socalled the "butterfly" diagram (e.g., Yoshimura 1975;Parker 1979;Rogachevskii & Kleeorin 2000;Kitchatinov 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6)− (8) it is seen that for the case of energy equipartition, ε = 1, the small-scale dynamo makes significant contributions to different parts of the MEMF. Kitchatinov (2002Kitchatinov ( , 2004 has found that anisotropic diffusion may be in a large part responsible for the equatorial drift of the toroidal LSMF. This drift is actually an extra diffusion (of both the toroidal and poloidal parts of the mean field) along the rotation axis e. In Eq.…”
Section: The Solar αmentioning
confidence: 99%
“…(1) which are of odd order in e, that is, the terms with coefficients f 1 will be referred to as anisotropic diffusion. The second part of this term, proportional to f (a) 1 (ε+1), is known to describe an extra diffusion along e (Kitchatinov et al 1994;Kitchatinov 2002Kitchatinov , 2004.…”
Section: Introductionmentioning
confidence: 99%